Diversity and temporal dynamics of breast milk microbiome and its influencing factors in Chinese women during the first 6 months postpartum - Liu, Bin; Zhao, Junying; Liu, Yanpin; Qiao, Weicang; Jiang, Tiemin; Chen, Lijun (Frontiers in Microbiology, 2022)
Human breast milk (HBM) plays an important role in providing nutrients, beneficial microorganisms and bioactive components for infants, helping maturation of their immune system and gastrointestinal development. Here, we present a study aiming to investigate the diversity and temporal dynamics of the milk microbiome across the first 6 mo postpartum in Chinese healthy breastfeeding women, and to investigate to what extent other variables (e.g., sampling location, infant sex, and mode of delivery) might also be related to variations in the human milk microbiome, and the association with maternal diet and nutrients. Fifty-three healthy pregnant women from four cities were recruited from a China Maternal and Infant Health Cohort Study and breast milk samples were collected and analyzed using 16S rRNA metagenomic sequencing. We illustrated the diversity and temporal dynamics during lactation (Adonis P-value = 3e-04). Firmicutes and Proteobacteria were the most abundant phyla, and Streptococcus, Staphylococcus, Serratia and Corynebacterium were the core genera. PAM clustering identified two major internal clusters of breast milk microbiota. Cluster 1 was dominated by Acinetobacter and Pseudomonas, while Cluster 2 was dominated by Streptococcus and Staphylococcus. Among other environmental variables, sampling location showed significant influence on breast milk microbiome (Adonis P-value = 4e-04), while infant sex (Adonis P-value = 0.33), and mode of delivery (Adonis P-value = 0.19) were less related to variations in the human milk microbiome. These results illustrated the dynamic changes of composition and diversity during the lactation stages of the Chinese breast milk microbiome and addressed the importance of geographic location on milk microbiota, and associations with maternal diet consumption, which have potential benefits on the establishment and future health of breastfeeding infants.